2003
DOI: 10.1103/physrevstab.6.054401
|View full text |Cite
|
Sign up to set email alerts
|

Landau damping via the harmonic sextupole

Abstract: Multibunch instabilities of a storage ring electron beam occur due to coherent particle oscillations generated through a bunch to bunch coupling via the impedances, deteriorating the beam quality. One cure for multibunch instabilities is Landau damping, i.e., introducing a spread in the oscillation frequencies among the particles of the individual bunches in order to destroy the coherence of the coupled multibunch oscillation. Measurements at ELETTRA have shown that the harmonic sextupole provides Landau dampi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The required spread of frequencies in the beam can be ensured by means of nonlinear elements of the magnetic lattice, namely, by octupoles and sextupoles. Octupoles involve an amplitude dependent shift of a betatron frequency as the first order effect, while sex tupoles (whose main effect on the beam is a frequency shift depending on a longitudinal momentum (for rel ativistic particles, on energy)) also introduce an amplitude dependent shift of a betatron frequency, which, as the investigations performed at an Elettra SR source of a third generation have shown [75]), may turn out to be sufficient to ensure the required spread of the frequencies. Since a multibunch instability can be considered as a set of two types of a collective motion of particles, i.e., oscillation of each bunch as a whole and oscillation of the particles inside the bunch, a principle question arises as to whether the reason for the multibunch instability suppression is a spread of frequencies between the bunches or inside each bunch.…”
Section: Transverse Multibunch Instabilitymentioning
confidence: 96%
See 3 more Smart Citations
“…The required spread of frequencies in the beam can be ensured by means of nonlinear elements of the magnetic lattice, namely, by octupoles and sextupoles. Octupoles involve an amplitude dependent shift of a betatron frequency as the first order effect, while sex tupoles (whose main effect on the beam is a frequency shift depending on a longitudinal momentum (for rel ativistic particles, on energy)) also introduce an amplitude dependent shift of a betatron frequency, which, as the investigations performed at an Elettra SR source of a third generation have shown [75]), may turn out to be sufficient to ensure the required spread of the frequencies. Since a multibunch instability can be considered as a set of two types of a collective motion of particles, i.e., oscillation of each bunch as a whole and oscillation of the particles inside the bunch, a principle question arises as to whether the reason for the multibunch instability suppression is a spread of frequencies between the bunches or inside each bunch.…”
Section: Transverse Multibunch Instabilitymentioning
confidence: 96%
“…Thus, the experimental study of transverse multi bunch instability of the beam in an Elettra storage ring [75] showed that instability can be efficiently sup pressed by decoherence of oscillations of the beam particles that is introduced by the family of harmonic sextupoles. The results of the study clarified that atten uation is caused by the spread of the frequencies of oscillations of the particles inside the bunch, and it may be efficient both in the cases of multibunch and single bunch instabilities.…”
Section: Transverse Multibunch Instabilitymentioning
confidence: 98%
See 2 more Smart Citations
“…At HLS, there haven't other reliable beam stabilizing measures, such as longitudinal and transverse feedback systems, non-uniform filling mode, except for Landau damping, which is coming from transverse tune spread and becomes a main stabilizing mechanism at storage ring. Usually, the second order effects of sextupoles, which used to compensate chromaticities or to enlarge dynamic aperture, would result in tune shift with amplitude in transverse planes [2,3] :…”
Section: Introductionmentioning
confidence: 99%